Handbook of semiconductor silicon technology / edited by William C. O'Mara, Robert B. Herring, Lee P. Hunt. - O'Mara, William C.; Herring, Robert B.; Hunt, Lee P. (Lee Philip) (Materials science and process technology series, 1990)
A summary of the science, technology, and manufacturing of semiconductor silicon materials. Properties of silicon are detailed, and a set of silicon binary phase diagrams is included. Other aspects such as materials handling, safety, impurity, and defect reduction are also discussed.